da Vinci robot-assisted keyhole neurosurgery: a cadaver study on feasibility and safety - Marcus,HJ; Hughes-Hallett,A; Cundy,TP; Yang,GZ; Darzi,A; Nandi,D (Neurosurgical Review, 2014)
The goal of this cadaver study was to evaluate the feasibility and safety of da Vinci robot-assisted keyhole neurosurgery. Several keyhole craniotomies were fashioned including supraorbital subfrontal, retrosigmoid and supracerebellar infratentorial. In each case, a simple durotomy was performed, and the flap was retracted. The da Vinci surgical system was then used to perform arachnoid dissection towards the deep-seated intracranial cisterns. It was not possible to simultaneously pass the 12-mm endoscope and instruments through the keyhole craniotomy in any of the approaches performed, limiting visualization. The articulated instruments provided greater dexterity than existing tools, but the instrument arms could not be placed in parallel through the keyhole craniotomy and, therefore, could not be advanced to the deep cisterns without significant clashing. The da Vinci console offered considerable ergonomic advantages over the existing operating room arrangement, allowing the operating surgeon to remain non-sterile and seated comfortably throughout the procedure. However, the lack of haptic feedback was a notable limitation. In conclusion, while robotic platforms have the potential to greatly enhance the performance of transcranial approaches, there is strong justification for research into next-generation robots, better suited to keyhole neurosurgery.